Analisis Kenakalan Remaja: Studi Kasus pada MAN 2 Padangsidimpuan - Nasution, Khadijah Rahmah; Hasibuan, Ali Daud (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
This study aims to analyze juvenile delinquency at MAN 2 Padangsidimpuan. It consists of the types of delinquency, the causal factors, and the efforts of the counseling teacher in alleviating juvenile delinquency. The research method used is descriptive qualitative. The research subjects were students, counseling teachers, subject teachers, homeroom teachers, and parents of students taken using the snowball sampling technique. Research instruments used observation, interviews, and documentation. Data analysis techniques used data reduction, data presentation, and drawing conclusions. The results of the study found: 1) Types of delinquency that occurred; smoking, skipping school, not doing homework, leaving the house without saying goodbye to parents, coming home late at night, fighting, bullying; 2) The factor of delinquency; environmental factors, wrong perceptions of subject teachers and learning activities, often delaying and neglecting assignments, lack of parental attention, abused solidarity, having wrong perceptions of others; 2) The efforts of the counseling teacher in alleviating juvenile delinquency are; providing information, supervising student activities through collaboration with subject teachers and parents, providing individual counseling services, group guidance, and content mastery services to improve student skills in certain fields. Keywords: Juvenile delinquency, the efforts of the counseling teacher